Upper limb injuries during the mens Field Hockey Junior World Cup 2009 - Mukherjee, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Field hockey players are at risk of upper limb injuries and the use of protective gear is uncommon in the sport. Despite the suggestive evidence, there are no reports on hand and upper limb injuries in elite youth hockey players during major international tournaments. The objective of this study was to provide a descriptive epidemiological account of upper limb injuries in elite youth male field hockey players during the Men`s Junior World Cup 2009. Methods: A total of 324 players were observed during 58 matches in the tournament. The injury reporting system was based on that used in team sports during international tournaments. All injury documentation was done by direct on-location observation by a trained sports medicine physician followed by confirmation from the team doctors or physiotherapists. Results: A total of 28 hand and upper limb injuries were documented in the 58 matches observed. The overall injury frequency rate was 19 per 1000 match hours and 22 per 1000 player matches. Most injuries (50%) were due to the ball striking the body part with hand being the commonest site (61%) and contusion being the commonest type (82%) of injury. The left hand and wrist was more commonly injured than the right side. The incidence of injuries was higher in the second-half (64%) than the first half. Fifty-four of the 324 athletes observed wore gloves on either left or both hands. Nineteen of the 20 hand/wrist injuries were in athletes not wearing gloves.